2019
DOI: 10.15226/csroa.2019.00147
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Radiosurgery Target Volume Determination for Meningiomas Based on Computed Tomography (CT) And Magnetic Resonance Imaging (MRI)

Abstract: Objective: Meningiomas arise from arachnoid cap cells and comprise the commonest benign tumor of the brain, accounting for more than one third of all intracranial neoplasms. Surgery and radiation therapy (RT) have been traditionally used in meningioma management. Radiosurgery is a sophisticated form of therapeutic irradiation with the capability of delivering high doses of radiation to well defined targets with typically steep dose gradients around the treatment volumes under robust stereotactic localization a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 33 publications
2
4
0
Order By: Relevance
“…Utility of multimodality imaging for radiosurgery treatment planning for tectal gliomas has been poorly addressed in the literature. In this context, our study adds to the existing literature and supports the incorporation of MRI for improved radiosurgery treatment planning for tectal gliomas consistent with another studies [48][49][50][51][52][53][54][55][56][57][58][59].…”
Section: Discussionsupporting
confidence: 86%
“…Utility of multimodality imaging for radiosurgery treatment planning for tectal gliomas has been poorly addressed in the literature. In this context, our study adds to the existing literature and supports the incorporation of MRI for improved radiosurgery treatment planning for tectal gliomas consistent with another studies [48][49][50][51][52][53][54][55][56][57][58][59].…”
Section: Discussionsupporting
confidence: 86%
“…In this study, we assessed incorporation of multimodality imaging into target volume definition of trigeminal neuralgia radiosurgery. Indeed, usefulness of neuroimaging with MRI for definition of central nervous system radiotherapy and radiosurgery target volumes has been an important focus of research in the literature [40][41][42][43][44][45][46][47][48][49]. Our results appear to be compatible to these studies supporting the incorporation of MRI in radiosurgery treatment planning.…”
Section: Discussionsupporting
confidence: 83%
“…In this context, multimodality imaging may add to the accuracy of target definition for radiosurgery of intracranial GCTs. Indeed several other studies have demonstrated refined treatment volume determination by including MRI to the process of target determination [39][40][41][42][43][44][45][46][47][48][49][50][51].…”
Section: Resultsmentioning
confidence: 99%